Modeling and simulation of an underactuated system - Nader K.; Sarsri D. (MATEC Web of Conferences, 2019)
One of the most active research areas in mechatronic systems is the control of mechanical systems controlled by electronic systems using computer programs. These programs execute algorithms called control laws. Our study focuses on the control of underactuated mechanical systems: Case of a reversed two-wheeled pendulum. It consists of developing a control law to stabilize this system. This class of system is rich in practical as well as theoretical applications (SEGWAY, Acrobot robots ...) and this is why the control synthesis for underactuated mechanical systems constitutes a very active research axis and still constitues an open domain for technological research.